A fire in the belly of Hineāmaru: a collection of narratives about Te Tai Tokerau tūpuna - Webber, Melinda; O'Connor, Te Kapua (Auckland University Press, 2022)
Keywords: history; kōrero nehe; kōrero taumata; northland; rangatira; tūpuna; whakapapa

Environmental politics and policy in Aotearoa New Zealand - Bargh, Maria; MacArthur, Julie (Auckland University Press, 2022)
Environmental Politics and Policy in Aotearoa New Zealand is a comprehensive introduction to confronting some of today's most urgent challenges. Global warming, threats to biodiversity, contamination of waterways and other environmental issues confront today's citizens with critical challenges that are fundamentally political. Power, authority and state action enable current practices - and through politics and policy that power can be harnessed to create a more ecologically sustainable planet. In this book, leading scholars from around Aotearoa introduce students to environmental politics and policy based in this country's unique institutional, cultural and resource context. The text focuses on the key importance of Te Tiriti o Waitangi, the characteristics of the natural environment in Aotearoa and the role of gender dynamics in the distribution of power, before turning to how this unique setting informs and is, in turn, informed by the global context of environmental politics. The authors take a systemic view of environmental politics and governance in New Zealand, addressing the philosophical and ideational debates about who and what matters (both human and non-human), the political institutions that embed and enact these ideas, and how these ideas then manifest in particular arenas - from climate and freshwater to energy and farming. Practical tips - how to make a submission, organise a protest, write a policy brief or a press release - are woven throughout.
Keywords: environment; environmental conditions; environmental protection; government relations; social conditions; tiriti o waitangi/treaty of waitangi